The Influence of Family Members’ Identification With the Firm on Family SME’s International Diversification: The Moderating Role of Exploration and Exploitation - Basly, Sami (Management international / International Management / Gestiòn Internacional, 2022)
This research investigates the effect of the key socio-emotional goal of family members’ identification with the firm on international diversification. Furthermore, it examines the moderating effect of a family firm’s learning orientation – expressed in terms of a firm’s exploratory and reproductive orientations – on the relationship between this goal and a firm’s degree of international diversification. Our findings do not validate the thesis according to which a reproductive orientation would reinforce the negative relationship between family members’ identification and international diversification. However, it shows that exploratory orientation negatively moderates the relationship between family members’ identification with the firm and international diversification.